STRATEGI KOMUNIKASI PEMASARAN POLITIK DALAM KAMPANYE CALON LEGISLATIF (CALEG) TERPILIH PARTAI PERSATUAN PEMBANGUNAN (PPP) DALAM PEMENANGAN PILEG 2014 KOTA PEKANBARU - Nita Ria Liliana; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Indonesian General Election 2014 is the 11th general election held in Indonesia. In the 2014 election, the PPP into 10 major parties and get the sequence number 9 (nine). In the 2014 Legislative elections, Chairman of the DPC PPP has a target to get 8 seats in Pekanbaru City Council of five constituencies. But only able to get four seats this increase, since the legislative elections of 2009 the PPP only get 3 seats. For this study aims to determine how the credibility of elected candidates of PPP, knowing how the process of marketing communication in the candidates and their campaign teams success in winning legislative elections in 2014 in the city of Pekanbaru and to know campaign techniques. This research method is a method of qualitative research agenda setting theory by Maxwell McCombs and L.Shaw. Investigation determination of the agenda (agenda setting) to view the functions of mass media in campaigning. Techniques of data collection is done through observation, interviews and documentation. Data analysis techniques include data reduction, data presentation and conclusion and verification. These results indicate that marketing communications in the legislative election campaign in 2014 in Pekanbaru City run by the elected candidates of PPP along with the success of the team operating effectively. The communication process is carried out very clear and to the point. Because of the vision, mission and programs delivered by the candidate and his campaign team greatly affect the public election region by providing support in the form of people's right to select the candidates.